(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with control mechanisms for the protection of human rights within the framework of regional organizations such as the Organization of American States, League of Arab States, the African Union and the Organization of Islamic Conference. It should be noted that the issue of protection of civil and political rights and freedoms, including at the regional level still is one of the unexplored, and is also an important issue. One characteristic of modern international law is its penetration in the regulation of domestic relations. The role of regional regulations on the protection of human rights in institutsionalizirovanii control mechanisms.